2017
DOI: 10.1371/journal.pone.0187656
|View full text |Cite
|
Sign up to set email alerts
|

The role of character positional frequency on Chinese word learning during natural reading

Abstract: Readers’ eye movements were recorded to examine the role of character positional frequency on Chinese lexical acquisition during reading and its possible modulation by word spacing. In Experiment 1, three types of pseudowords were constructed based on each character’s positional frequency, providing congruent, incongruent, and no positional word segmentation information. Each pseudoword was embedded into two sets of sentences, for the learning and the test phases. In the learning phase, half the participants r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…According to the following criteria which were same as that in Experiment 1 ( Rayner et al, 2006 ; Bai et al, 2008 ; Rayner, 2009 ; Li et al, 2017 ; Liang et al, 2017 ; Wang et al, 2018 ), analysis data was selected. After excluding invalid data (1.65% of the total data), data analysis was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…According to the following criteria which were same as that in Experiment 1 ( Rayner et al, 2006 ; Bai et al, 2008 ; Rayner, 2009 ; Li et al, 2017 ; Liang et al, 2017 ; Wang et al, 2018 ), analysis data was selected. After excluding invalid data (1.65% of the total data), data analysis was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…The overall pattern emerging from these studies is that children read more slowly than adults, tend to make shorter saccades, fixate words more frequently and for a longer time, and show higher regression probabilities, but lower word skipping rates (see Reichle et al, 2013, for a summary). These effects are consistently found and have been observed in languages as diverse as English (Blythe et al, 2006;Blythe et al, 2015;Milledge et al 2021), Finnish (Häikiö et al, 2009), German (Huestegge et al, 2009;Rau et al, 2014;Tiffin-Richards & Schroeder, 2015a), French (Mancheva et al, 2015), Chinese (Blythe et al, 2012;Chen & Ko, 2011;Zang et al, 2013;Liang et al, 2015Liang et al, , 2017Liang et al, , 2021, and Japanese (Jincho et al, 2014).…”
Section: Cross-linguistic Differences In Reading Developmentmentioning
confidence: 87%
“…By contrast, if spaces are artificially introduced between words, reading is facilitated for children [50,51] and learners of Chinese as a second language [52]. Furthermore, it has been demonstrated that Chinese readers use statistical lexicality cues (i.e., some characters are more likely to be a single character word-single character word likelihood [53]; and some characters are more likely to appear at the beginning or end of a word-within word character positional frequency [54][55][56]) to facilitate word segmentation processes during reading.…”
Section: The Current Challenge: the Concept Of A Word And Its Role Inmentioning
confidence: 99%